Anomeric stereospecific synthesis of 2 '-C-methyl beta-nucleosides; the Holy reaction of cyanamide with 2-C-methyl-D-arabinose - Jenkinson, S; Jones, N; Moussa, A; Stewart, A; Heinz, T; Fleet, G (2007)
The sequential reactions of 2-C-methyl-d-arabinose with cyanamide and methyl propiolate afford an anhydronucleoside, which may be opened under acid conditions with inversion at C2′, to give 2′-C-methyl uridine; ring opening with sodium hydroxide gave 2′-C-methyl arabino-uridine with retention of configuration at C2′. This gives complete stereospecific control to yield only β-nucleosides. © 2007 Elsevier Ltd. All rights reserved.